STOP Glaucoma in Sub Saharan Africa: enhancing awareness, detection, management, and capacity for glaucoma care. (4th May 2017) - Damji, Karim F.; Nazarali, Samir; Giorgis, Abeba; Kiage, Dan; Marco, Sheila; Philippin, Heiko; Daniel, Neema; Amin, Samreen
ABSTRACT: Introduction : Glaucoma in Sub Saharan Africa (SSA) poses a daunting challenge. Communities are often unaware of the serious implications of glaucoma and are faced with limited access to specialists, making early detection and management difficult. For those who have been diagnosed, socioeconomic barriers limit access to treatment. Since 2006, we have been involved in an innovative program we term 'STOP Glaucoma in SSA'. The four main pillars of this program include building capacity, enhancing awareness, and improving glaucoma detection and management. The aim of this initiative is to train the first generation of highly qualified glaucoma subspecialist leaders and to develop centers of excellence for glaucoma care throughout SSA that are interconnected. Our ultimate aim is to reduce the burden of blindness from glaucoma in SSA. Areas covered : Our review addresses background context, provides learning from the first decade of this program, and offers solutions to help tackle the scourge of glaucoma in SSA. Expert commentary : Research in ocular genetics, primary congenital glaucoma, ophthalmic nanomedicine, and cost effective therapies will continue to improve our understanding of glaucoma as well as access to quality care for glaucoma in SSA.